Contrast and Conflict in Dutch Vowels - de Rue, Nadine P. W. D.; Snijders, Tineke M.; Fikkert, Paula (Frontiers in Human Neuroscience, 2021)
The nature of phonological representations has been extensively studied in phonology and psycholinguistics. While full specification is still the norm in psycholinguistic research, underspecified representations may better account for perceptual asymmetries. In this paper, we report on a mismatch negativity (MMN) study with Dutch listeners who took part in a passive oddball paradigm to investigate when the brain notices the difference between expected observed vowels. In particular, we tested discrimination of the tense mid vowel pairs /o/-/ø/ (place contrast), /e/-/ø/ (labiality contrast), and /e/-/o/ (place and labiality contrast). Our results show (a) a perceptual asymmetry for place in the /ø/-/o/ contrast, supporting underspecification of [CORONAL] and replicating earlier results for German, and (b) a perceptual asymmetry for labiality for the /e/-/ø/ contrast, which was not reported in the original German study. A labial deviant [ø] (standard /e/) yielded a larger MMN than a deviant [e] (standard /ø/). No asymmetry was found for the two-feature contrast. This study partly replicates a similar MMN study on German vowels, and partly presents new findings indicating cross-linguistic differences. Although the set of vowels in Dutch and German are to a large extend comparable, their (morpho)phonological systems are different, which is reflected in processing.